1997
DOI: 10.1080/026990597123386
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse, traumatic brain injury and neuropsychological outcome

Abstract: The neuropsychological performance of 119 patients with severe closed traumatic brain injury (TBI) who had received toxicology screens at the time of trauma centre admission was examined. Three groups were created: normal screen, positive alcohol screen, or positive abused drugs screen (with or without the presence of alcohol). The admitting Glasgow Coma Scale (GCS) score was significantly lower in the positive alcohol screen group than the normal screen group, while the three groups did not differ in length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 39 publications
5
54
1
Order By: Relevance
“…However, a history of chronic alcohol abuse in these intoxicated patients predicted a worse outcome compared with no previous alcohol exposure. In a retrospective study of 380 head-injured patients, Kelly et al 24 found no difference in traumatic lesion size of intoxicated head injured patients when compared with nonintoxicated patients; about 82% of this patient group sustained minor head injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, a history of chronic alcohol abuse in these intoxicated patients predicted a worse outcome compared with no previous alcohol exposure. In a retrospective study of 380 head-injured patients, Kelly et al 24 found no difference in traumatic lesion size of intoxicated head injured patients when compared with nonintoxicated patients; about 82% of this patient group sustained minor head injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an animal model investigation, acute ethanol administration actually had a protective effect in reducing cognitive deficits following TBI (Janis et al, 1998). In contrast, a recent study Kelly et al (1997) found greater neuropsychological deficits in substance abusers who sustained a TBI than TBI subjects without substance abuse. Such contrasting findings underscore the need to carefully examine the putative deleterious role that substance abuse may play in TBI outcome.…”
Section: Performance On Neuropsychological Measuresmentioning
confidence: 74%
“…However, the relationship between TBI and substance abuse has not been well defined. Also, only limited attention has been paid to the role of intoxication or substance abuse in neuropathological and cognitive sequelae as well as rehabilitation outcome associated with cerebral injury (Bogner et al, 1997;Brooks et al, 1989;Corrigan, 1995;Emmerson et al, 1988;Kelly et al, 1997;Sander et al, 1997;Solomon & Malloy, 1992;Sparadeo & Gill, 1989;Rönty et al, 1993). This is often the case because patients with substance abuse problems are excluded from TBI studies to control for effects of preinjury conditions (Dicker, 1989;Kaplan & Corrigan, 1992;Robertson et al, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…However, it is not yet clear from the extant clinical literature whether people who have consumed alcohol prior to their injury have better or worse outcomes than those who have not. At a glance, the findings appear quite disparate, with evidence that alcohol both decreases (e.g., Berry et al, 2010;Berry et al, 2011;Raj et al, 2015) and increases (e.g., Chapital et al, 2007;Sparadeo & Gill, 1989) mortality rates, and is associated with a range of cognitive changes (Bombardier & Thurber, 1998;Kaplan & Corrigan, 1992;Kelly, Lee, Pinanong, & Hovda, 1997;Lange, Iverson, & Franzen, 2008;Wilde et al, 2004). Similarly, there are studies that show no difference in outcomes (e.g., Alexander et al, 2004;Chen et al, 2012;Matsukawa et al, 2013) and others that suggest that outcomes may be dose-dependent (e.g., Tien et al, 2006), with alcohol potentially being neuroprotective at low to moderate levels and neurotoxic at high levels (Chen et al, 2012;Tien et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…In particular, it is unclear whether the subtle cognitive problems that were observed here predated the current injury, possibly due to prior alcohol abuse and/or previous TBI. General information relating to pre-injury alcohol use/abuse was only reported in 37% of cases, with most of these studies including some people who had a history of alcohol abuse and others recognising that their inability to report this information was a limiting factor (Alexander et al, 2004;Berry et al, 2010;Kelly, Johnson, Knoller, Drubach, & Winslow, 1997). Although restricting our ability to identify the source of the cognitive problems, the inclusion of people with pre-injury alcohol abuse meant that the current findings better reflect the diversity of people seen in clinical situations.…”
Section: Limitations and Future Researchmentioning
confidence: 99%